Boosting the Performance of ZnO/CdS Core‐Shell Nanorod Array‐based Solar Cells by ZnS Surface Treatment. Issue 9 (21st July 2015) - Kamble, Archana; Sinha, Bhavesh B.; Chung, Kookchae; Mali, Sawanta S.; Agawane, Ganesh L.; Vanalakar, Sharad A.; Kim, In Young; Hong, C. K.; Kim, J. Y.; Kim, Jin Hyeok; Patil, Pramod S.
Abstract With a view to enhancing the efficiency of ZnO/CdS core‐shell nanorod array‐based semiconductor sensitized solar cells (SSSCs), ZnS surface treatment is envisioned. It is achieved through a thin layer of ZnS being deposited onto ZnO/CdS film by a successive ionic layer adsorption and reaction (SILAR) technique. To ascertain the optimum thickness of ZnS and to enhance the solar cell performance, we have varied the number of SILAR cycles of ZnS deposition. The optimized film is then considered for structural, morphological, and electrochemical studies. The analysis reveals the benefits of ZnS surface treatment on ZnO/CdS core‐shell photoelectrodes in terms of an enhancement of solar cell performance of up to 1.54 % from 1.23 %.